Determinantes de la Rentabilidad en la Banca Privada del Ecuador - Iñiguez González, Henry Patricio (2024)
The concept of profitability becomes relevant for companies and organizations in different industries, especially in the financial industry, since the efficient allocation of resources to different agents promotes investment, production and social economic development of an environment, it is therefore necessary to establish the determinants of profitability of private banks in Ecuador, this being the objective of this research. In this way, inputs are obtained that serve for the construction of strategies that enhance the efficiency of banking operations and remain sustainable in the market, guaranteeing the continuity of economic growth. The methodology used had a mixed approach that started with the descriptive scope and reached the explanatory one, using econometrics where a multiple linear regression model is applied with the variables, asset quality, liquidity, total late payments, total coverage, financial intermediation, income, investments and gross portfolio to estimate the profitability obtained as a function of assets and capital. The study covers the period from 2003 to 2022. The units of analysis correspond to the 24 private banks in Ecuador, whose information was obtained from the statistical portal of the Superintendency of Banks. The results reveal that private banks have been progressively efficient in the profitability of their assets, valuing the presence of a range of products and services in a competitive environment. Similarly, it was determined that there is a direct relationship between profitability and variables such as asset quality, total late payments, total coverage, financial intermediation and investments, while the gross portfolio variable shows a significant inverse relationship with profitability. In conclusion, the improvement strategies directed to the significant variables should be effective to promote the progress of the banking institutions and these strategies increase their profitability.